The Interaction of Air Pollutant Molecules with Germanene and Silicene: a Density Functional Theory Study - Muhammad Rifqi Al Fauzan; Wijayanti Dwi Astuti; Ghorby Al Fauzan; Sholihun Sholihun (Molekul, 2018)
We investigate the adsorption of atmospheric pollutants on germanene and silicene using density functional theory (DFT) calculations. In this study, we use carbon monoxide (CO) and nitric oxide (NO) as the pollutant molecules. Electronic properties of germanene and silicene are explored to obtain a good understanding in the adsorption process. Our calculation results show both germanene and silicene provide an identical mechanism of adsorption. Germanene and silicene adsorb CO and NO spontaneously with physisorption and chemisorption types for CO and NO molecules, respectively. We also conduct the Mulliken charges calculations to evaluate the transformation of atomic charges due to the adsorption process. From Mulliken charge calculation results we can confirm the existence of charge transfer between the adsorbent materials and the pollutant molecules. This phenomenon lies behind the occurrence of the adsorption process.